2008
DOI: 10.1111/j.1742-1241.2008.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and alpha-melanocyte-stimulating hormone: interaction in obesity and possible role in the development of hypertension

Abstract: Alterations in leptin, NPY and a-MSH are frequently observed in obesity and might stimulate SNS activity, contributing to the development of hypertension in obese patients. These neuropeptides might provide a pathophysiologic link between excess weight and hypertension. However, more research is needed before the pharmacologic manipulation of these complex neuroendocrine systems can be applied in the treatment of obesity and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 128 publications
(195 reference statements)
0
34
0
2
Order By: Relevance
“…That is to say, it is the brain's response to the environment, more so that the environment itself, that dictates the full metabolic outcome of environmental changes such as the presentation of the westernized diet. The neurophysiological literature is now replete with studies demonstrating the important roles of several neural circuits that impact peripheral fuel metabolism (reviewed in [32]) including hypothalamic arcuate-alpha melanocortin-stimulating hormone (αMSH) [33][34][35] and arcuate neuropeptide Y (NPY) -paraventricular nuclei (PVN) circuits [36][37][38], the lateral hypothalamic (LH) leptinorexin mesolimbic circuit [39][40][41][42], ventromedial hypothalamic and arcuate leptin autonomic/neuroendocrine circuits [43][44][45][46][47], and the insulin arcuate [48] and dopamine mesolimbic circuits [49,50] to name just a few. Emerging experimental evidence suggests important roles for the biological clock system residing within and around the SCN of the hypothalamus in the integration of these CNS circuits to create an orchestrated organized CNS output signal (program) to the peripheral organs respecting fuel metabolism (see discussion below) [51][52][53][54].…”
Section: Evolution Of Insulin Resistance and Its Potentiation By The mentioning
confidence: 99%
“…That is to say, it is the brain's response to the environment, more so that the environment itself, that dictates the full metabolic outcome of environmental changes such as the presentation of the westernized diet. The neurophysiological literature is now replete with studies demonstrating the important roles of several neural circuits that impact peripheral fuel metabolism (reviewed in [32]) including hypothalamic arcuate-alpha melanocortin-stimulating hormone (αMSH) [33][34][35] and arcuate neuropeptide Y (NPY) -paraventricular nuclei (PVN) circuits [36][37][38], the lateral hypothalamic (LH) leptinorexin mesolimbic circuit [39][40][41][42], ventromedial hypothalamic and arcuate leptin autonomic/neuroendocrine circuits [43][44][45][46][47], and the insulin arcuate [48] and dopamine mesolimbic circuits [49,50] to name just a few. Emerging experimental evidence suggests important roles for the biological clock system residing within and around the SCN of the hypothalamus in the integration of these CNS circuits to create an orchestrated organized CNS output signal (program) to the peripheral organs respecting fuel metabolism (see discussion below) [51][52][53][54].…”
Section: Evolution Of Insulin Resistance and Its Potentiation By The mentioning
confidence: 99%
“…For example, endogenous opioid neuropeptides consisting of enkephalin, endorphin, and dynorphins are important for mediating stress and analgesia in disease as well as in healthy conditions (14,47). NPY regulates feeding behavior and obesity (17,18,48,49); cholecystokinin regulates anxiety and related behaviors (50). Galanin participates in regulating cognition and is involved in Alzheimer disease that results in severe memory loss (51).…”
Section: Substratementioning
confidence: 99%
“…Cathepsin V resides with enkephalin and NPY in secretory vesicles where neuropeptides are produced. Furthermore, cathepsin V expression with proNPY results in production of cellular NPY, a brain peptide responsible for feeding behavior and obesity (17,18), and in the peripheral sympathetic nervous system NPY participates in stress and blood pressure regulation (18,19). These significant findings demonstrate participation of human cathepsin V in the production of enkephalin and NPY neuropeptides that are essential for peptide neurotransmission in health and disease.…”
Section: Proteases Are Required For Processing Precursors Into Activementioning
confidence: 99%
“…For instance, Coelho et al (2004) reported that two receptors implicated in the action of NPY are involved in the development of hypertension in rats. Furthermore, it has been shown that plasma NPY concentrations are higher in hypertensive individuals (Baltatzi et al 2008(Baltatzi et al , 2011, and a functional polymorphism in the NPY gene has been associated with hypertension (Ilveskoski et al 2008;Bhaskar et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NPY has been linked with blood pressure (BP) (Baltatzi et al 2008), PYY has been associated with glucose metabolism and insulin resistance (Boey et al 2007;Ukkola et al 2011), and leptin may have multiple effects on lipid metabolism (Lago et al 2009). …”
Section: Introductionmentioning
confidence: 99%